Lead and cadmium uptake by sunflower from contaminated soil and remediated with organic amendments in the form of compost and vermicompost - Munive, Rubén (2020)
In order to reduce heavy metal contamination in agricultural soils, we decided to assess the effect of organic amendments (compost and vermicompost). The work was carried out using sunflower as a fitorremediator. For this purpose, the agricultural soils of the Mantaro and Muqui localities of the Mantaro Valley were used. The results indicate that the soils of the locality of Muqui, contain the greatest amount of Pb and Cd, presenting negative effects on biomass production. The sunflower plant absorbs heavy metals as evidenced by the increased accumulation of lead and cadmium at the root of the sunflower, no significant differences were found between the accumulation of lead in stems and flowers, stems and leaves, for cadmium on the stems and leaves, confirming that the application of organic amendments contributes to solubilizing the Pb and Cd of the soil, in addition to contributing to further development of the crop. Cadmium Bioconcentration Factor (BCF) values (0.53 - 0.66) were better than lead (0.07 - 0.08), while Translocation Factor (FT) values indicated a sunflower capacity as a phytostabilizer, especially with the use of vermicompost (Pb: 1.2 - Cd: 1.4) in compost (Pb: 0.8 - Cd: 1.2).